The Hill and the Asphalt: A 50-year perspective on informality in Rio de Janeiro - Perlman, Janice (Ciência & Trópico, 2020)
This article argues that informality is essential to urban vitality and that the ability of the formal sector to function depends upon the labour, consumer strength, social resilience, and intellectual capital of the people considered marginal. Based on the author’s 50 years of original fieldwork in the favelas of Rio de Janeiro, she takes exception to the much-touted goal of ‘Cities without Slums’, contending that cities without slums are cities without soul. What should be eradicated is not informality, but poverty, inequality, and exclusion. Her research findings reveal what has changed in the case of Rio’s favelas, by following hundreds of families over four generations. She chronicles the evolution of favela policy from hostile to hopeful and back again – with the return of favela removal and the sabotaging of promising upgrading, public safety, and social projects. The result of policies over the last 20 years has been to increase spatial and socio-economic segregation, which in turn, has increased lethal violence. This trend has made vulnerability a chronic condition in informal communities in the south and precarious neighbourhoods in the north, eroding a sense of security and of self. The chapter concludes with the provocation to go beyond territorial place-based thinking to poverty-based remediation and rights-based approaches including the right to the city and the universal right to dignity for all.